Program Multi Level Marketing Generasi Berencana Kabupaten Pasuruan Perspektif Maslahah Mursalah - Murti, Fitria Dwi; Chudlori, Zayin (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This article discusses the theory of mashlahah mursalah on the Multi Level Marketing Planning Generation Program (MLM Genre) of the Family Planning and Women's Empowerment Office in Pasuruan Regency. From the research on the MLM Genre program organized by the Family Planning and Women's Empowerment Office of Pasuruan Regency, it can be concluded: First, this program has not been implemented properly because the program should have been implemented in every sub-district in Pasuruan Regency, which amounted to twenty-four Districts, but for now it is still running in five districts only. Among the factors is the lack of awareness of the Pasuruan community to participate in running the program. Second, the Multi Level Marketing Planning Generation Program organized by the Family Planning and Women's Empowerment Office of Pasuruan Regency in terms of activities and material delivered by the Family Planning and Women's Empowerment Office of Pasuruan Regency provides benefits for adolescents and the surrounding community who will get married. In the perspective of the maslahah mursalah, it has fulfilled the requirements of the mashlahah, and does not contradict to the texts, real, general in nature, and has many benefits. [Artikel ini membahas tentang Analisis Maslahah Mursalah terhadap Program Multi Level Marketing Generasi Berencana (MLM Genre) Dinas Keluarga Berencana dan Pemberdayan Parempuan di Kabupaten Pasuruan. Dari penelitian mengenai program MLM Genre yang diselenggarakan oleh Dinas Keluarga Berencana dan Pemberdayaan Perempuan Kabupaten Pasuruan dapat disimpulkan: Pertama, program ini belum terlaksana dengan baik karena yang seharusnya program tersebut dilaksanakan di setiap kecamatan yang ada di Kabupaten Pasuruan yang berjumlah dua puluh empat Kecamatan, namun untuk saat ini masih berjalan di lima kecamatan saja, di antara faktornya adalah kurangnya kesadaran masyarakat Pasuruan untuk berpartisipasi dalam menjalankan program tersebut. Kedua, program Multi Level Marketing Generasi Berencana yang diselenggarakan oleh Dinas Keluarga Berencana dan Pemberdayaan Perempuan Kabupaten Pasuruan dilihat dari segi kegiatan maupun dari materi yang disampaikan oleh Dinas Keluarga Berencana dan Pemberdayaan Perempuan Kabupaten Pasuruan memberikan manfaat bagi remaja dan masyarakat sekitarnya yang akan melangsungkan pernikahan. Dalam perspektif maslahah mursalah telah memenuhi syarat syarat Maslahah mursalah yaitu tidak bertentangan dengan nash atau dalil dalil qath’i, bersifat nyata, bersifat umum, dan memiliki banyak kemaslahatan.]